Complex engineering service systems concepts and research - Ng, Irene C. L.; SpringerLink (Online service). (London New York Springer, 2011)
For manufacturers of complex engineering equipment, the focus on service and achieving outcomes for customers is the key to growth. Yet, the capability to provide service for complex engineered products is less understood. Taking a trans-disciplinary approach, Complex Engineering Service Systems covers various aspects of service in complex engineering systems, with perspectives from engineering, management, design, operations research, strategy, marketing and operations management that are relevant to different disciplines, organisation functions, and geographic locations. The focus is on the many facets of complex engineering service systems around a core integrative framework of three value transformations ? that of material/equipment, information and people. Complex Engineering Service Systems is the outcome of the EPSRC/BAE Systems S4T (Service Support Solutions: Strategy and Transition) research programme of 10 universities and 27 researchers, which examined how high-value manufacturers of complex engineering products adapt to a multi-partnered environment to design and deliver value in a service system. Complex Engineering Service Systems aims to be the main source of knowledge for academics and professionals in the research and practice of contracting, managing, designing, leading, and delivering complex engineering service systems. The book takes a value-based approach to integrating equipment and human factors into a total service provision. In doing so, it aims to advance the field of service systems and engineering.
1. Service Enterprise Transformation -- 2. Enterprise Imaging: Visualising the Scope and Dependencies of Complex Service Enterprises -- 3. Complexity Management -- 4. Towards Understanding the Value of the Client?s Aspirations and Fears in Complex, Long-term Service Contracts -- 5. Redefining Organisational Capability for Value Co-creation in Complex Engineering Service Systems -- 6. Service Uncertainty and Cost for Product Service Systems (PSS) -- 7. Incentives and Contracting for Availability: Procuring Complex Performance (PCP) -- 8. Behaviour Transformation: An Examination of Relational Governance in Complex Engineering Service -- 9. A Framework for Service Information Requirements -- 10. Investigating the Role of Information on Service Strategies Using Discrete Event Simulation -- 11. A Blueprint for Engineering Service Definition -- 12. Contracting for Availability and Capability in the Defence Environment -- 13. Enabling Support Solutions in the Defence Environment -- 14. Modelling Techniques to Support the Adoption of Predictive Maintenance -- 15. Component Level Replacements: Estimating Remaining Useful Life -- 16. Scheduling Asset Maintenance and Technology Insertions -- 17. Simulation Based Process Design Methods for Maintenance Planning -- 18. Integrated Approach to Maintenance and Capability Enhancement -- 19. Mapping Platform Transformations -- 20. Service Thinking in Design of Complex Sustainment Solutions -- 21. Towards Integrative Modelling of Service Systems.
"... is the outcome of the EPSRC/BAE Systems S4T (Service Support Solutions: Strategy and Transition) research programme of 10 universities and 27 researchers"--Back cover.
Electronic reproduction.
Keywords: Engineering services marketing; Electronic books